Climate-smart house: Housing that is cyclone resistant and food, energy and water efficient in Bangladesh - WorldFish (2014)
Since cyclones Sidr (2007) and Aila (2009), communities in southern Bangladesh have increasingly needed to protect their homes and livelihoods from destructive natural disasters. WorldFish embarked on a climate-resilient housing project in 2013, building a prototype climate-smart house that is resilient to cyclones and is also water, food, energy and space efficient.